The Development of Managerial Culture A Comparative Study of Australia and Canada - Wolak, Arthur J. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
The Development of Managerial Culture examines the differences in underlying values and cultural distinctions in managerial cultures in Australia and Canada. It offers commentary on differences in attitudes to managerial culture and industrial relations through a comparison of national character development to provide context and insight for readers.